A Comparative Transcriptome Analysis Revealing the Mechanism Underlying the Effect of Maternal Plant Age on Adventitious Rooting of Euryodendron excelsum Cuttings - Ji Li; Xinyi Liu; Kunlin Wu; Shasha Wu; Junwen Zhai; Lin Fang; Songjun Zeng (Horticulturae)
Euryodendron excelsum H. T. Chang, a monotypic plant endemic to China, exhibits significant variations in adventitious root formation in cuttings across different age groups through unclear molecular mechanisms. In this study, we performed RNA-sequencing (RNA-seq) and data analysis at three stages—initial excision (S0), root primordia (S1), and emergence of adventitious roots (S2)—for lateral buds from transplanted triennial tissue culture seedlings and decennial E. excelsum plants. We identified 13,424 differentially expressed genes (DEGs) between different rooting stages and age groups, including 8216 upregulated and 5208 downregulated genes. A Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis indicated that the S1 and S2 DEGs identified were mainly involved in phenylpropanoid biosynthesis, plant hormone signal transduction, plant–pathogen interactions, biosynthesizing various secondary plant metabolites, and starch and sucrose metabolism. Key auxin-pathway genes were expressed at significantly higher levels in culture seedlings than in adult plants, as were WUSCHEL-related homeobox and LATERAL ORGAN BOUNDARIES DOMAIN genes (related to adventitial root growth and development), which together promote the formation, growth, and development of adventitial root primordia. The dysregulated expression of 15 DEGs identified by RNA-seq were verified via real-time quantitative polymerase chain reaction analysis. This study investigates the morphological processes of adventitious root formation in cuttings of E. excelsum of different ages, and the potential molecular mechanisms involved. Our finding provides a basis for research on cutting propagation, conservation applications, and optimization of tissue culture for E. excelsum, and may help improve the rooting rate of E. excelsum cuttings.